2017
DOI: 10.1063/1.4979199
|View full text |Cite
|
Sign up to set email alerts
|

Fermi resonance in CO2: Mode assignment and quantum nuclear effects from first principles molecular dynamics

Abstract: Vibrational spectroscopy is a fundamental tool to investigate local atomic arrangements and the effect of the environment, provided that the spectral features can be correctly assigned. This can be challenging in experiments and simulations when double peaks are present because they can have different origins. Fermi dyads are a common class of such doublets, stemming from the resonance of the fundamental excitation of a mode with the overtone of another. We present a new, efficient approach to unambiguously ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Our simulations are compared to the perturbative expressions derived by Basire et al in Ref. 52 for the amplitude of the Fermi splitting in the classical (dashed line) and in the quantum (continuous line) frameworks. As in ref.…”
Section: Fermi Resonancesmentioning
confidence: 97%
See 2 more Smart Citations
“…Our simulations are compared to the perturbative expressions derived by Basire et al in Ref. 52 for the amplitude of the Fermi splitting in the classical (dashed line) and in the quantum (continuous line) frameworks. As in ref.…”
Section: Fermi Resonancesmentioning
confidence: 97%
“…In ref. 52, Basire et al developed a different perturbative approach and showed that the temperature-dependence of this splitting is qualitatively different if the system is treated classically or quantummechanically, accounting for zero-point motion. Indeed, the classical Fermi splitting goes to zero as T 1/2 at low temperature while the quantum one saturates at a non-zero value.…”
Section: Fermi Resonancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermi resonances occur when a stretch mode of frequency Ω 1 splits by coming into resonance with a bend overtone of frequency 2Ω 2 ≃ Ω 1 . A simple model of a Fermi resonance, which is sufficient to demonstrate the failure of classical and path-integral methods to predict the splitting, is 32,54 H =Ĥ (0) +V (1) ,…”
Section: Fermi Resonancesmentioning
confidence: 99%
“…Tests on simple models have shown that path-integral methods essentially reproduce the classical splittings, 6,32 which agree with the quantum splittings at high temperatures, but underestimate them at low temperatures, predicting an erroneous T 1/2 dependence. 54 In Section IV, we show numerically that this failing is also caused by the neglect of 'Matsubara heating', whereby the coupling of the fluctuation modes increases the amplitudes of the perturbed centroid vibrations. Further possible examples of dynamics which could be affected by coupling between the centroid and fluctuation modes are discussed briefly in Section V, which concludes the article.…”
Section: Introductionmentioning
confidence: 99%